2018
DOI: 10.1002/cbic.201700553
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Algae by Chemical Surface Engineering

Abstract: Chemical cell-surface engineering is a tool for modifying and altering cellular functions. Herein, we report the introduction of an antibiotic phenotype to the green alga Chlamydomonas reinhardtii by chemically modifying its cell surface. Flow cytometry and confocal microscopy studies demonstrated that a hybrid of the antibiotic vancomycin and a 4-hydroxyproline oligomer binds reversibly to the cell wall without affecting the viability or motility of the cells. The modified cells were used to inhibit bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…It was previously demonstrated that the exposure of the microalgae to high concentration of antibiotic induces the loss of flagella. [60] As growth was not impaired, we hypothesize that loss of flagella function could be the explanation for the reduced phototaxis response of microalgae modified with 0.04 mM of antibiotics in our experiments.…”
Section: Figurementioning
confidence: 80%
See 2 more Smart Citations
“…It was previously demonstrated that the exposure of the microalgae to high concentration of antibiotic induces the loss of flagella. [60] As growth was not impaired, we hypothesize that loss of flagella function could be the explanation for the reduced phototaxis response of microalgae modified with 0.04 mM of antibiotics in our experiments.…”
Section: Figurementioning
confidence: 80%
“…[58] Additionally, the negatively charged C. reinhardtii cell wall was used for the modification of interacting surfaces by electrostatic interactions. For example, the coating of the microalgae surface was achieved with chitosan, [27] 4-hydroxyproline (4-HP)-rich polypeptides, [59,60] or magnetic microbeads. [61] Covalent attachment of artificial metalloenzymes [57] and antibiotics [62] were recently reported by our group.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“… 205 This living functionalized algae carrier was chosen as it is biodegradable 206 and does not trigger immune response in mice, 207 and chemical engineering of the surface had been demonstrated previously. 208 The algae were functionalized using the well-established DBCO handle, allowing for copper-free azide–alkyne cycloaddition. Vancomycin was modified at the C-terminus via the installation of a PEG spacer containing the photocleavable o -nitrobenzyl moiety and a terminal azide handle.…”
Section: Recent Developments In Semisynthetic Glycopeptide Antibioticsmentioning
confidence: 99%
“…Applying this method, selective incorporation of azide moieties on the surface of tumor cells both in vitro and in vivo could be achieved. [35] In the context of our research program on surface engineering with new-to-nature catalyst systems, [36] antibiotics, [37,38] proteins, [39] to biohybrid microswimmers, [40] we became interested in antibody recruiting to cell surfaces.…”
Section: Introductionmentioning
confidence: 99%